Ceftriaxone Potentiates Warfarin Activity Greater Than Other Antibiotics in the Treatment of Urinary Tract Infections. (April 2016) - Saum, Lindsay M.; Balmat, Ryan P.
Background: The cephalosporin class has been associated with an increased risk of bleeding among elderly patients receiving warfarin. Urinary tract infections (UTI) are the most prevalent infection in elderly patients. Objective: To determine the extent of interaction between antibiotics used in the treatment of UTI, particularly specific cephalosporins and warfarin. Methods: A retrospective chart review was conducted on chronic warfarin patients with a diagnosis of UTI treated with ceftriaxone, a first-generation cephalosporin, penicillin, or ciprofloxacin. The primary outcome was the comparison of the extent of international normalized ratio (INR) change from baseline between each antibiotic group. Results: The ceftriaxone group was found to have a statistically significant higher peak INR value compared to all other studied antibiotics (ceftriaxone: 3.56, first-generation cephalosporins: 2.66, penicillins: 2.98, ciprofloxacin: 2.3; P = .004), a statistically significant greater extent of change in INR value (+1.19, +0.66, +0.8, +0.275; P = .006), and a statistically significant greater percentage change in INR value when compared to ciprofloxacin (54.4% vs 12.7%; P = .037). Conclusion: Ceftriaxone interacts with warfarin to increase a patient's INR value more than other commonly administered antibiotics for UTI treatment. Other antibiotics should be preferred for UTI treatment in patients on warfarin.